Characteristics of major sports injuries in high-performance athletes - Sun, Y. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction The focus of attention in high-performance athlete injuries tends to be on physical recovery, neglecting psychological factors and their practical social impacts on the rehabilitation of the injured athlete. In this phase, giving attention to the importance of athletes` thoughts, emotions, and motivation can speed up the biopsychosocial rehabilitation process. Objective To analyze the characteristics involved in the major sports injuries of high-level athletes to provide a reference for athletes and coaches during recovery. Methods This article analyzes through bibliographic research the characteristics of the major sports injuries in high-level athletes, including physiological, psychological, and social factors. Results The physical impact of injuries requires patience and persistence for recovery, including additional muscle strengthening to compensate for the loss of residual joint proprioception, ensuring performance recovery. Mental factors such as insecurity when returning from games, reduced self-confidence, and fear of hurting the team must be worked through in parallel in multi-professional care and during long recovery periods. Conclusion Sports injuries can occur in athletes of all levels. For elite athletes, the impact of injuries, especially severe ones that need to interrupt training or even surgery, will lead to forced suspension of training or competition, preventing the improvement of sports performance, decreasing the quality of the sports career, and may even lead to physical or psychological disability in severe cases.